Penelopa i jej współczesne filmowe inkarnacje - Rojek, Patrycja (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
Penelope and Her Cinematic Incarnations By analysing contemporary cinematic incarnations of Penelope, the wife of Odysseus, the author shows a thematic relation between cinema and ancient mythologies. Although an interest in mythical motifs is visible in film from its very beginnings, their popularity has constantly changed due to e.g., technological developments in filmmakers’ capabilities. However, what never changes is the presence of mythical plots in deeper story structures, which include the recreation of ancient characters. Examining Penelope’s spirit in today’s culture proves that the mythical story in which she appears provides excellent material for building new things – it easily adapts to modern times, constantly inspires artists, and stimulates various reflections about our cultural heritage.